Three Essays Unpacking the Role of Cross-Cultural Experience on Entrepreneurship - Pidduck, Robert John (My University, 2019)
This dissertation comprises three essays probing the underlying mechanisms in the relationship between cross-cultural experience and entrepreneurship. Decades of research across multiple disciplines have provided evidence that various forms of cross-cultural experience can be personally transformative and have constructive implications for both businesspeople and their firms. Only recently, however, has entrepreneurship research started to examine how interactions with different cultures can not only stimulate people to launch firms, but also help people better develop their new ventures. These three essays advance theory in this nascent yet growing area by taking a cognitive lens to delineate what it is about the root phenomena—exposure to different cultures—that can be a potent driver of entrepreneurial activity. In a world of ever growing global connectivity and international mobility, and with increasingly idiosyncratic forms of cross-cultural exposure available to prospective entrepreneurs, my dissertation helps us to understand how we can leverage this influential form of experience to foster innovative entrepreneurship.
Keywords: Entrepreneurship; Cross-Cultural Experience; Entrepreneurial Capabilities